Reliable cooperative data transmission mechanism for wireless sensor networks - ZHANG Shu-kui; FAN Jian-xi; CUI Zhi-ming (Tongxin xuebao)
The efficient data transmission problem through cooperative communication was studied,a network coding was designed with random binning implements for wireless sensor networks,a cooperative data transmission scheme combined with the network coding was proposed,analyzed the end-to-end outage probability was analyzed.the usefulness of relaying was evaluated,and an ACK-less data transmission method based on the cooperative mechanism was developed.The theoretical analysis and experimental simulations show that they allowing for a more efficient use of resources.